2016
DOI: 10.1186/s40064-016-2554-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of school desk on the learning of graphic skills in early childhood education in Brazil

Abstract: The role of two different layouts of school furniture was investigated in the pattern legibility and spatial–temporal parameters of a graphic skill acquisition. Thirty children from the first grade of elementary school (mean age = 6 years) practiced a graphic task according to a criterion figure. They were assigned to two groups, Group of Fixed School Desk (GF) and Group with Adjustable School Desk (GA). Each child practiced the task on a digital tablet for 25 trials. The software Movalyser 2.3 processed the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The research-literature for kindergarten furniture is relatively small, mainly in the field of storage, sitting furniture, activity area furniture, and interior space-related design studies (Cheng et al 2019). The design strategy is mainly reflected in the playful, guidance, modularity, safety, fun, growth, and emotional design methods (Purwaningrum et al 2015;Gimenez et al 2016). Fun and emotionality are concentrated in the color, shape, and material performance of kindergarten furniture.…”
Section: Research On the Design Of Kindergarten Furniturementioning
confidence: 99%
“…The research-literature for kindergarten furniture is relatively small, mainly in the field of storage, sitting furniture, activity area furniture, and interior space-related design studies (Cheng et al 2019). The design strategy is mainly reflected in the playful, guidance, modularity, safety, fun, growth, and emotional design methods (Purwaningrum et al 2015;Gimenez et al 2016). Fun and emotionality are concentrated in the color, shape, and material performance of kindergarten furniture.…”
Section: Research On the Design Of Kindergarten Furniturementioning
confidence: 99%
“…Giraldi, L. et al [14] optimized furniture, products, and graphics in preschool environments from the perspective of real attitudes, emotions, and abilities in children's lives, and proposed a set of good practices suitable for kindergarten environments, effectively improving children's educational experience. Gimenez, R. et al [15] investigated the role of two different layouts of school furniture in the pattern legibility and spatial-temporal parameters of graphic skill acquisition. Research has found that adjustable desks facilitate the acquisition of clear graphic patterns and can enhance children's handwriting and drawing skills.…”
Section: Kindergarten Furniture Designmentioning
confidence: 99%
“…The linear error is calculated by the length of a straight line in centimeters. The linear spatial error is calculated by the linear size difference in centimeters between the model figure and the actual drawing performed (Gimenez, Santos, Ojeda, Makida-Dionísio, & Manoel, 2016). It is like putting the drawing or activity on a straight line and calculating the errors, that is, the parts that protrude from that straight line (Codogno, 2011).…”
Section: Procedures For Data Analysismentioning
confidence: 99%